CHARACTER ANALYSIS IN “BABURNOMA”: IN THE EXAMPLE OF KHADICHABEGIM - Barotova Khurshida Jalolovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article discusses the skill of Zahiriddin Muhammad Babur, a young king and a fine poet, the owner of great talent, in creating the image of Sultan Hussein Boykara and his beloved wife Khadichabegim. The inhuman qualities characteristic of princess Khadichabegim, who was punished according to her actions, were deeply analyzed based on the information of "Boburnoma". Major historians of Babur Mirza's time, Mirza Muhammad Haidar, Ghiyaziddin ibn Humomiddin Khondamir, treated the personality of Khadija Begim in a comparative-typological direction with the interpretations in "Boburnoma".